A kind of polydicyclopentadiene material and preparation method thereof
By adding silane coupling agent to the polydicyclopentadiene material to modify montmorillonite and vinyl polysiloxoborane, the problem of poor flame retardant performance of the polydicyclopentadiene material is solved, and the high flame retardant grade and good mechanical properties of the material are achieved.
Patent Information
- Application Number
- CN202510029172.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-08
AI Technical Summary
Polybicyclopentadiene materials have poor flame retardant properties, resulting in poor performance in impact toughness and yield strength.
A new composite material is formed by adding a silane coupling agent to the polydicyclopentadiene material. The process includes mixing dicyclopentadiene, a modified montmorillonite-supported catalyst and vinyl polysiloxborane, followed by mixing with a cocatalyst and a relieving agent, and performing insulation molding to prepare a polybicyclopentadiene material.
This method significantly improves the flame retardant grade of polydicyclopentadiene material, making it reach V-0 grade, while maintaining high mechanical properties, including impact resistance and corrosion resistance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer-based composite materials, and in particular relates to a polydicyclopentadiene material and a preparation method thereof. Background Art
[0002] Polydicyclopentadiene is an engineering plastic with both impact resistance and modulus, which is polymerized by dicyclopentadiene monomer under the action of a catalyst. Its monomer dicyclopentadiene is a byproduct with a large output in the production of petrochemical ethylene. Polydicyclopentadiene engineering plastic has good heat resistance, creep resistance, dimensional stability, shape memory, corrosion resistance, light weight and other characteristics. It can be used to manufacture various high-performance, high-value-added, high-grade fine products.
[0003] Since polydicyclopentadiene is a full carbon chain polymer, it is very easy to burn. In order to improve the flame retardant properties of polydicyclopentadiene, it is necessary to add a flame retardant to improve the flame retardant properties of polydicyclopentadiene during the preparation process of polydicyclopentadiene. Conventional inorganic flame retardants are added in large quantities to cause the material to be reduced, and the excellent performance of polydicyclopentadiene in terms of impact toughness and yield strength cannot be fully utilized. The patent application with publication number CN104558326A discloses a flame retardant, a preparation method and a modified polydicyclopentadiene composite material, a preparation method, in which hexachlorocyclotriphosphazene is used as a matrix, a group with a dicyclopentadiene structure is connected to make it soluble in dicyclopentadiene, and it is copolymerized with dicyclopentadiene to prepare a flame-retardant polydicyclopentadiene composite material, which solves the problems that the existing insoluble flame retardant is not conducive to the reaction injection molding process of dicyclopentadiene, the mechanical property declines and the flame retardant effect is not good, but the introduction of halogen in the patent application will produce toxic gases in the combustion process. Summary of the invention
[0004] The object of the present invention is to provide a polydicyclopentadiene material and a preparation method thereof, so as to solve the problem that the polydicyclopentadiene material has poor flame retardancy.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A polydicyclopentadiene material comprises the following raw materials in parts by weight: 130-140 parts of dicyclopentadiene, 6.5-7 parts of vinyl polysiloxane, 6.5-7 parts of silane coupling agent modified montmorillonite, 0.4 parts of main catalyst, 0.8 parts of co-catalyst and 1 part of retarder.
[0007] As a further preferred solution of the present invention, the main catalyst is tungsten hexachloride; the co-catalyst is diethylaluminum monochloride; and the retarder is one of p-benzoquinone and n-butyl ether. The retarder can reduce the polymerization activity by complexing with the co-catalyst, thereby prolonging the gel time for easy processing.
[0008] As a further preferred embodiment of the present invention, the mass ratio of silane coupling agent to montmorillonite in the raw material for preparing silane coupling agent modified montmorillonite is 4-5:100. Ethanol, water and silane coupling agent are mixed and stirred for 2 hours, montmorillonite is added and stirred for 15 minutes, and then allowed to stand for 1-2 hours, and silane coupling agent modified montmorillonite is obtained by suction filtration, washing and drying. The standing time can be 1 hour, 2 hours, 3 hours or any value between the two ranges to achieve a full reaction between the raw materials. Montmorillonite can catalyze the polymer to form a carbon layer at high temperature. This carbon layer has good insulation and mass transfer barrier properties, can improve the flame retardancy of the material, and at the same time delay the escape of volatile products generated by thermal decomposition of the material.
[0009] As a further preferred embodiment of the present invention, the silane coupling agent is one of KH-550, KH-560 and KH-570.
[0010] As a further preferred embodiment of the present invention, vinyl polysiloxane is prepared by the following steps:
[0011] Phenylboric acid and 1,2-dichloroethane are mixed under inert gas or nitrogen protection conditions, 1,2-dichloroethane dissolved with KH-570 is added dropwise, and the reaction is heated. After the reaction is completed, 1,2-dichloroethane is removed by rotary evaporation to obtain vinyl polysiloxane. The solvent can be 1,2-dichloroethane, the reaction temperature can be 40, 50, 60, 70, 80°C or any value between the two ranges, and the reaction time can be 4h, 5h, 6h, 7h, 8h or any value between the two ranges, so that the raw materials can react fully. The generated vinyl polysiloxane can have the effect of condensed phase and gas phase flame retardancy in the polymer matrix. The combination of vinyl polysiloxane and montmorillonite can improve the flame retardancy of the material.
[0012] As a further preferred embodiment of the present invention, the molar ratio of phenylboric acid to KH-570 is 2-3:1.
[0013] A method for preparing a polydicyclopentadiene material comprises the following steps:
[0014] Dicyclopentadiene, modified montmorillonite loaded catalyst and vinyl polysiloxaborane are mixed to obtain component A; dicyclopentadiene and vinyl polysiloxaborane, a co-catalyst and a retarder are mixed to obtain component B; component A and component B are mixed and injected into a mold, and heat-insulated and formed to obtain a polydicyclopentadiene material. By loading the catalyst first, it is more conducive to the stripping of montmorillonite, forming a more tortuous maze path, blocking the entry of corrosive media, improving the corrosion resistance of the material, and improving the mechanical properties of the material.
[0015] As a further preferred embodiment of the present invention, the modified montmorillonite supported catalyst is prepared:
[0016] Under the protection of inert gas or nitrogen, the main catalyst, toluene and silane coupling agent modified montmorillonite are mixed, ultrasonically shaken, toluene is removed, and the modified montmorillonite supported catalyst is obtained.
[0017] As a further preferred embodiment of the present invention, the mass ratio of dicyclopentadiene in component A to component B is 1:1; the mass ratio of vinyl polysiloxane in component A to component B is 1:1.
[0018] As a further preferred embodiment of the present invention, the insulation temperature is 68-70° C. and the insulation time is 30-40 min.
[0019] Beneficial effects of the present invention:
[0020] The addition of the silane coupling agent modified montmorillonite and vinyl polysiloxane added in the present invention enables the flame retardant grade of the material to reach V-0, and the mechanical properties of the material are less affected. The performance of the material can also be improved by controlling the ratio between different raw materials.
[0021] In the present invention, a silane coupling agent is added to modify the montmorillonite, the compatibility of the montmorillonite with the polymer matrix is improved, the interfacial force between the montmorillonite and the polymer matrix is improved, and after the main catalyst of the montmorillonite modified by the silane coupling agent is loaded, the polymerization reaction is more likely to occur between the sheets of the montmorillonite, which is convenient for the formation of a multiple cross-linking system, more conducive to the stripping formation of the montmorillonite, and the corrosion resistance of the material is improved. In the present invention, the treated montmorillonite is more likely to be entangled and cross-linked with the molecular chain of polydicyclopentadiene to form physical and chemical cross-linking points, which can further improve the mechanical properties of the material.
[0022] The present invention also adds vinyl polysiloxane to increase the viscosity in the initial stage of processing, ensuring sufficient time to fill the mold and improving processing performance. The introduction of vinyl polysiloxane benzene rings can introduce Si-OBO segments into the polydicyclopentadiene chain segments while maintaining basic tensile strength, thereby increasing the flexibility of the molecular chain and improving impact resistance. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1, preparation of polydicyclopentadiene material:
[0025] The preparation method comprises the following steps:
[0026] By weight, 130 parts of dicyclopentadiene, 6.5 parts of vinyl polysiloxane borane, 6.5 parts of silane coupling agent modified montmorillonite, 0.4 parts of main catalyst, 0.8 parts of co-catalyst and 1 part of retarder were weighed.
[0027] Silane coupling agent modified montmorillonite is prepared by the following steps:
[0028] Ethanol, water and silane coupling agent were mixed and stirred for 2 hours, montmorillonite was added and stirred for 15 minutes, and then allowed to stand for 2 hours. The silane coupling agent-modified montmorillonite was obtained by suction filtration, washing and drying, wherein the silane coupling agent was KH-550, and the mass ratio of ethanol, water, silane coupling agent and montmorillonite was 60:20:4:100.
[0029] Vinyl polysiloxane was prepared by the following steps:
[0030] Under nitrogen protection, phenylboric acid and 1,2-dichloroethane were mixed, and 1,2-dichloroethane dissolved with KH-570 was added dropwise. After the addition, the temperature was raised to 40°C and the reaction was carried out for 8 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain vinyl polysiloxane. The molar ratio of phenylboric acid to KH-570 was 2:1.
[0031] Under nitrogen protection, the main catalyst is tungsten hexachloride, toluene and silane coupling agent modified montmorillonite are mixed, ultrasonically shaken for 30 minutes, and the solvent is removed to obtain a modified montmorillonite-supported catalyst. 50% of the total amount of dicyclopentadiene, the modified montmorillonite-supported catalyst and 50% of the total amount of vinyl polysiloxane are mixed to obtain component A; the amount of toluene is based on the amount that can cover the silane coupling agent modified montmorillonite.
[0032] The remaining dicyclopentadiene and vinyl polysiloxane, the co-catalyst diethylaluminum chloride and p-benzoquinone are mixed to obtain component B; the components A and B are mixed and injected into a mold, and the temperature is maintained at 68-70° C. for 30 minutes during the process to obtain a polydicyclopentadiene material.
[0033] Example 2, preparation of polydicyclopentadiene material:
[0034] The preparation method comprises the following steps:
[0035] By weight, 135 parts of dicyclopentadiene, 6.5 parts of vinyl polysiloxane borane, 7 parts of silane coupling agent modified montmorillonite, 0.4 parts of main catalyst, 0.8 parts of co-catalyst and 1 part of retarder were weighed.
[0036] Silane coupling agent modified montmorillonite is prepared by the following steps:
[0037] Ethanol, water and silane coupling agent were mixed and stirred for 2 hours, montmorillonite was added and stirred for 15 minutes, and then allowed to stand for 2 hours. The silane coupling agent-modified montmorillonite was obtained by suction filtration, washing and drying, wherein the silane coupling agent was KH-550, and the mass ratio of ethanol, water, silane coupling agent and montmorillonite was 60:20:4:100.
[0038] Vinyl polysiloxane was prepared by the following steps:
[0039] Under nitrogen protection, phenylboric acid and 1,2-dichloroethane were mixed, and 1,2-dichloroethane dissolved with KH-570 was added dropwise. After the addition, the temperature was raised to 40°C and the reaction was carried out for 8 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain vinyl polysiloxane. The molar ratio of phenylboric acid to KH-570 was 2:1.
[0040] Under nitrogen protection, the main catalyst is tungsten hexachloride, toluene and silane coupling agent modified montmorillonite are mixed, ultrasonically shaken for 30 minutes, and the solvent is removed to obtain a modified montmorillonite-supported catalyst. 50% of the total amount of dicyclopentadiene, the modified montmorillonite-supported catalyst and 50% of the total amount of vinyl polysiloxane are mixed to obtain component A; the amount of toluene is based on the amount that can cover the silane coupling agent modified montmorillonite.
[0041] The remaining dicyclopentadiene and vinyl polysiloxane, the co-catalyst diethylaluminum chloride and p-benzoquinone are mixed to obtain component B; the components A and B are mixed and injected into a mold, and the temperature is maintained at 68-70° C. for 30 minutes during the process to obtain a polydicyclopentadiene material.
[0042] Example 3, preparation of polydicyclopentadiene material:
[0043] The preparation method comprises the following steps:
[0044] By weight, 140 parts of dicyclopentadiene, 7 parts of vinyl polysiloxane borane, 7 parts of silane coupling agent modified montmorillonite, 0.4 parts of main catalyst, 0.8 parts of co-catalyst and 1 part of retarder were weighed.
[0045] Silane coupling agent modified montmorillonite is prepared by the following steps:
[0046] Ethanol, water and silane coupling agent were mixed and stirred for 2 hours, montmorillonite was added and stirred for 15 minutes, and then allowed to stand for 2 hours. The silane coupling agent-modified montmorillonite was obtained by suction filtration, washing and drying, wherein the silane coupling agent was KH-550, and the mass ratio of ethanol, water, silane coupling agent and montmorillonite was 60:20:4:100.
[0047] Vinyl polysiloxane was prepared by the following steps:
[0048] Under nitrogen protection, phenylboric acid and 1,2-dichloroethane were mixed, and 1,2-dichloroethane dissolved with KH-570 was added dropwise. After the addition, the temperature was raised to 40°C and the reaction was carried out for 8 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain vinyl polysiloxane. The molar ratio of phenylboric acid to KH-570 was 2:1.
[0049] Under nitrogen protection, the main catalyst is tungsten hexachloride, toluene and silane coupling agent modified montmorillonite are mixed, ultrasonically shaken for 30 minutes, and the solvent is removed to obtain a modified montmorillonite-supported catalyst. 50% of the total amount of dicyclopentadiene, the modified montmorillonite-supported catalyst and 50% of the total amount of vinyl polysiloxane are mixed to obtain component A; the amount of toluene is based on the amount that can cover the silane coupling agent modified montmorillonite.
[0050] The remaining dicyclopentadiene and vinyl polysiloxane, the co-catalyst diethylaluminum chloride and p-benzoquinone are mixed to obtain component B; the components A and B are mixed and injected into a mold, and the temperature is maintained at 68-70° C. for 30 minutes during the process to obtain a polydicyclopentadiene material.
[0051] Example 4
[0052] Compared with Example 1, the present embodiment replaces the silane coupling agent modified montmorillonite with the silane coupling agent modified montmorillonite prepared in the following steps:
[0053] Ethanol, water and silane coupling agent were mixed and stirred for 2 hours, montmorillonite was added and stirred for 15 minutes, and then allowed to stand for 2 hours. The silane coupling agent-modified montmorillonite was obtained through suction filtration, washing and drying, wherein the silane coupling agent was KH-560, and the mass ratio of ethanol, water, silane coupling agent and montmorillonite was 60:20:4:100.
[0054] The remaining raw materials and preparation process remain the same as in Example 1.
[0055] Example 5
[0056] Compared with Example 1, the present embodiment replaces the silane coupling agent modified montmorillonite with the silane coupling agent modified montmorillonite prepared in the following steps:
[0057] Ethanol, water and silane coupling agent were mixed and stirred for 2 hours, montmorillonite was added and stirred for 15 minutes, and then allowed to stand for 2 hours. The silane coupling agent-modified montmorillonite was obtained through suction filtration, washing and drying, wherein the silane coupling agent was KH-570, and the mass ratio of ethanol, water, silane coupling agent and montmorillonite was 60:20:4:100.
[0058] The remaining raw materials and preparation process remain the same as in Example 1.
[0059] Example 6
[0060] Compared with Example 1, in this example, the vinyl polysiloxane is replaced with the vinyl polysiloxane prepared in the following steps:
[0061] Under nitrogen protection, phenylboric acid and 1,2-dichloroethane were mixed, and 1,2-dichloroethane dissolved with KH-570 was added dropwise. After the addition, the temperature was raised to 40°C and the reaction was carried out for 8 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain vinyl polysiloxane. The molar ratio of phenylboric acid to KH-570 was 3:1.
[0062] The remaining raw materials and preparation process remain the same as in Example 1.
[0063] Comparative Example 1
[0064] Compared with Example 1, the comparative example is that the montmorillonite modified by the silane coupling agent is replaced by the montmorillonite not modified by the silane coupling agent, and the other raw materials and preparation process remain the same as those in Example 1.
[0065] Comparative Example 2
[0066] Compared with Example 1, in this comparative example, the silane coupling agent-modified montmorillonite is replaced by montmorillonite not modified by the silane coupling agent, and the amount of the montmorillonite not modified by the silane coupling agent is reduced to 3 parts, and the other raw materials and preparation process remain the same as in Example 1.
[0067] Comparative Example 3
[0068] Compared with Example 1, the vinyl polysiloxane in this comparative example is replaced by the vinyl polysiloxane prepared in the following steps:
[0069] Under nitrogen protection, phenylboric acid and 1,2-dichloroethane were mixed, and KH-570 was dissolved in the reagent 1,2-dichloroethane. After the addition, the temperature was raised to 40°C and the reaction was carried out for 8 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain vinyl polysiloxane. The molar ratio of phenylboric acid to KH-570 was 1:2.
[0070] The remaining raw materials and preparation process remain the same as in Example 1.
[0071] Comparative Example 4
[0072] Compared with Example 1, this comparative example does not add vinyl polysiloxane, and the remaining raw materials and preparation process remain the same as those of Example 1.
[0073] Performance tests were performed on Examples 1 to 6 and Comparative Examples 1 to 4. The bending and tensile performance tests of the tested samples were performed using an AGS-X10KN Shimadzu universal testing machine, wherein the bending test specimen was 4 mm × 10 mm × 60 mm, the tensile test specimen was a 4 mm × 10 mm dumbbell-shaped specimen, and the impact test specimen was a 4 mm × 10 mm × 60 mm notched specimen. The results are shown in Table 1:
[0074]
[0075] As can be seen from Table 1, the polydicyclopentadiene material prepared by the present invention has good mechanical properties. The addition of vinyl polysiloxane and alkane coupling agent modified montmorillonite enhances the tensile strength, flexural strength and impact resistance of the sample to be tested. It is known that the type of silane coupling agent in the silane coupling agent modified montmorillonite is adjusted to affect the performance of the polydicyclopentadiene material sample, wherein KH-570 is selected, that is, the silane coupling agent with vinyl is selected to be more conducive to improving the mechanical properties of the material. The added vinyl polysiloxane can be used to improve the viscosity in the early stage of processing, ensure that there is enough time to fill the mold, improve processing performance, and the introduction of vinyl polysiloxane is conducive to improving the crosslinking density, the introduction of vinyl polysiloxane benzene ring, while maintaining basic tensile strength, introduces Si-OBO segments in the segments of polydicyclopentadiene, increases the flexibility of the molecular chain, and improves impact resistance. However, the proportion of vinyl in vinyl polysiloxane should not be too much, and too much addition will lead to reunion, resulting in a decrease in the impact resistance of the material.
[0076] Corrosion resistance test: soak the sample in a 30% nitric acid solution at 30°C for 24 hours, and record the mass change rate of the sample; Flame retardant performance test: measure according to standard GB / T2408-2021; the results are shown in Table 2 below:
[0077]
[0078] As can be seen from Table 2, the addition of the silane coupling agent modified montmorillonite and vinyl polysiloxane added in the present invention makes the flame retardant grade of the material reach V-0, and the mechanical properties of the material have little influence, and the performance of the material can also be improved by controlling the ratio between different raw materials. More prominent is the corrosion resistance and flame retardant properties of the polydicyclopentadiene material prepared by the present invention. According to Example 1-Example 6, it is known that montmorillonite can better improve corrosion resistance after treatment, and the C=C double bond in the polydicyclopentadiene material is easily oxidized, which can cause the mass change rate of the material to be higher, and the corrosion resistance is reduced, resulting in a decrease in the mechanical properties of the material. The treated montmorillonite in the present invention is more likely to be entangled and cross-linked with the molecular chain of polydicyclopentadiene, forming physical and chemical crosslinking points, and the polymerization reaction after loading by the main catalyst of the silane coupling agent modified montmorillonite is more likely to occur between the sheets of montmorillonite, which is convenient for the formation of a multiple cross-linking system, and is more conducive to realizing the peeling formation of montmorillonite, forming a more tortuous maze path, blocking the entry of corrosive media, and improving the corrosion resistance of the material.
[0079] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polydicyclopentadiene material, characterized in that: The invention comprises the following raw materials in parts by weight: 130-140 parts of dicyclopentadiene, 6.5-7 parts of vinyl polysiloxane, 6.5-7 parts of silane coupling agent-modified montmorillonite, 0.4 parts of main catalyst, 0.8 parts of co-catalyst and 1 part of retarder; the vinyl polysiloxane is prepared by the following steps: Under the protection of inert gas or nitrogen, phenylboric acid and 1,2-dichloroethane are mixed, 1,2-dichloroethane dissolved with KH-570 is added dropwise, and heated for reaction. After the reaction is completed, 1,2-dichloroethane is removed by rotary evaporation to obtain vinyl polysiloxane; the molar ratio of phenylboric acid to KH-570 is 2-3:1; The polydicyclopentadiene material is prepared by the following steps: Under the protection of inert gas or nitrogen, the main catalyst, toluene and montmorillonite modified by silane coupling agent are mixed, ultrasonically shaken, toluene is removed, and a modified montmorillonite-supported catalyst is obtained; Dicyclopentadiene, modified montmorillonite supported catalyst and vinyl polysiloxane are mixed to obtain component A; dicyclopentadiene, vinyl polysiloxane, a co-catalyst and a retarder are mixed to obtain component B; component A and component B are mixed and injected into a mold, and heat-insulated and formed to obtain a polydicyclopentadiene material.
2. A polydicyclopentadiene material according to claim 1, characterized in that: The main catalyst is tungsten hexachloride; the co-catalyst is diethylaluminum monochloride; and the retarder is one of p-benzoquinone and n-butyl ether.
3. A polydicyclopentadiene material according to claim 1, characterized in that: The mass ratio of the silane coupling agent to the montmorillonite in the raw materials for preparing the silane coupling agent modified montmorillonite is 4-5:
100.
4. A polydicyclopentadiene material according to claim 1, characterized in that: The silane coupling agent is one of KH-550, KH-560 and KH-570.
5. A method for preparing the polydicyclopentadiene material according to any one of claims 1 to 4, characterized in that: The steps include: Under the protection of inert gas or nitrogen, the main catalyst, toluene and montmorillonite modified by silane coupling agent are mixed, ultrasonically shaken, toluene is removed, and a modified montmorillonite-supported catalyst is obtained; Dicyclopentadiene, modified montmorillonite supported catalyst and vinyl polysiloxane are mixed to obtain component A; dicyclopentadiene, vinyl polysiloxane, a co-catalyst and a retarder are mixed to obtain component B; component A and component B are mixed and injected into a mold, and heat-insulated and formed to obtain a polydicyclopentadiene material.
6. The method for preparing the polydicyclopentadiene material according to claim 5, characterized in that: The mass ratio of dicyclopentadiene in component A and component B is 1:1; the mass ratio of vinyl polysiloxane in component A and component B is 1:
1.
7. The method for preparing the polydicyclopentadiene material according to claim 5, characterized in that: The insulation temperature is 68-70℃ and the insulation time is 30-40min.
Citation Information
Patent Citations
Flame retardant, preparation method, flame retardant modified polydicyclopentadiene composite and preparation method
CN104558326A
Intrinsic flame-retardant polydicyclopentadiene elastomer material and preparation method thereof
CN115746204A
Degradable polydicyclopentadiene thermosetting material containing silyl ether element and preparation method of degradable polydicyclopentadiene thermosetting material
CN117343235A